Minding and Caring about Ethics in Brain Injury - Gillett, Grant (The Hastings Center report, 2016)
Joseph Fins's book Rights Come to Mind: Brain Injury, Ethics, and the Struggle for Consciousness (Cambridge UP, 2015) is a considerable addition to the literature on disorders of consciousness and the murky area of minimally conscious states. Fins brings to this fraught area of clinical practice and neuroethical analysis a series of stories and reflections resulting in a pressing and sustained ethical challenge both to clinicians and to health care systems. The challenge is multifaceted, with diagnostic and therapeutic demands to be met by clinicians and a mix of moral, scientific-economic, and political resonances for health care analysts. Everything in the book resonates with my own clinical experience and the often messy and emotionally wrenching business of providing ongoing care for patients with severe brain injuries and disorders, people who frequently resist the categorizations that well-organized health care systems prefer and that can dictate terms of patient management.